2020
DOI: 10.3390/ani10020329
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thymol and Thymol α-D-Glucopyranoside on Intestinal Function and Microbiota of Weaned Pigs

Abstract: The present study evaluated gluco-conjugation as a measure to delay thymol absorption and enhance its antimicrobial activity in the gut of weaned piglets. The three dietary treatments consisted of a basal diet without additives (TCON), supplemented with thymol at 3.7 mmol/kg dry matter (TTHY), or with an equimolar amount of thymol α-D-glucopyranoside (TTαG). Each dietary treatment was replicated in 6 pens with 2 piglets per pen (n = 12 for analytical parameters) and was supplemented for 14 days. The total (fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…It is reported that when feeding weaned pigs with unprotected thymol, around 75% free thymol appears in the stomach, and thymol is hardly detected in the small intestine 26 . Even though thymol is undetectable in the small intestine, weaned pigs with thymol supplementation have a lower diarrhea incidence and less watery feces compared to control pigs 27 . Compositions of gut microbiota are modulated in these thymol‐fed pigs as well.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that when feeding weaned pigs with unprotected thymol, around 75% free thymol appears in the stomach, and thymol is hardly detected in the small intestine 26 . Even though thymol is undetectable in the small intestine, weaned pigs with thymol supplementation have a lower diarrhea incidence and less watery feces compared to control pigs 27 . Compositions of gut microbiota are modulated in these thymol‐fed pigs as well.…”
Section: Discussionmentioning
confidence: 99%
“…Studies involving pigs revealed that a mix of thyme and peppermint essential oils and a plant extract of oregano had a positive effect on the microbiological profile of the large intestine, which was manifested by a significant increase in the count of probiotic bacteria (Ruzauskas et al, 2020). Thymol fed to piglets decreased the count of Escherichia coli in the proximal part of the small intestine compared to control piglets (Van Noten et al, 2020).…”
Section: Herbal Active Substancesmentioning
confidence: 99%
“…The mid-colon refers to a 20-cm section cranial to the end of the centripetal coils of the colon. After weaning, the pig was fed a cereal-soy-based weaner (2 weeks) and starter (4 weeks) diet without antimicrobial growths promoters or probiotics until collection (Table 1 in Van Noten et al, 2020 [24]). After euthanasia, the abdominal cavity of the pig was opened, and the mid-colonic section was clamped with forceps and excised.…”
Section: Incubation Strategymentioning
confidence: 99%